SISTEM PAKAR IDENTIFIKASI KERUSAKAN MOTOR KAWASAKI NINJA 250 CC DENGAN METODE FORWARD CHANNING BERBASIS ANDROID - Efrianto, Rian Dwi; Fajrin, Alfannisa Alfannisa (LPPM Universitas Putera Batam, 2019)
Refers to the times, expert systems have been used in various fields. In its use an expert system is a system developed to include expert thinking in solving problems in a field into a technology-based application or system. Seeing the many uses of motorized vehicles, in this study the expert system will be used as a solution to the problem of damage to the 250cc Ninja Kawasaki motor vehicle. This expert system is designed with an androidbased application and will identify existing damage based on the symptoms that will appear on the application screen and selected by the 250cc Kawasaki Ninja motorcycle users who want to repair the damage to the motorbike. Identification data and symptoms used are data from the company's mechanical staff who work directly with the motor of the brand. This expert system application is also built with the forward chaining method and using Android studio as a developer application